Enhance User Interface to Deaf E-Learning Based on User Centered Design - Fardan Zamakhsyari; Achmad Teguh Wibowo; Mohammad Khusnu Milad (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2022)
Abstract—The cognitive learning approach through visual media is a characteristic of learning for deaf students because these students can receive learning more quickly. However, this method became an obstacle when this process was online conducted because of the effect of the Covid-19 pandemic. Based on the explanation, a need for media learning based on interactive media can help students in the studying process. This research focuses on developing learning media using User Center Design (UCD) method to a center for the development system. In this research, we develop a user interface (UI) for deaf students, especially in the Putra Asih inclusive school in the city of Kediri, Indonesia. The evaluation of this research using ISO-9241 shows the effectiveness of using the application obtained 87,15%, effectiveness of the user interface design obtained 80,05%, and user satisfaction obtained 71,18% where all parameters make sense and acceptable based on a response from the users.